The Framework of Handling Sexual Violence in Indonesian Universities - Hermawati, Yanti; Widiyanto, Widiyanto; Santoso, Edy; Nuryanti, Nuryanti (Komunitas, 2023)
Prior to the promulgation of the Regulation of The Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia (Mendikbudristek) Number 30 of 2021, several universities have established a procedure of preventing and handling sexual violence cases in their respective domains. The promulgation has since encouraged commitment of these institutions to actively tackle the issue. This article elaborates the patterns of handling of sexual violence in seven Indonesian universities using qualitative method and pragmatic approach. Instead of addressing to certain theories, this method focuses on providing answers for a concrete issue. The researchers obtained the data by conducting in-depth interviews, focus group discussion, and document analysis. As results, there are two categories of status, including the institutions that had already assembled a special task force for preventing and handling sexual violence prior to the issuance of the regulation and the institutions that had not. From these two categories, the researchers found three patterns and propose a framework for handling of sexual violence in Indonesian universities. The designed model is based on a compilation of various handling procedures, implemented best practices, and violence prevention measures in higher education. It complements the already implemented procedures in accordance with regulations.. It is hoped that this framework will assist universities that do not yet have or need to change their procedures for addressing sexual violence.